Maternidad y poder en la dramaturgia limeña contemporánea - Torres Vilar, Natalia (2014)
Gender roles have been redefining their place in society, and this has generated difficulties regarding the equilibrium between women´s right to procreate and the abuse of their power over this. Using a qualitative design and assuming that a cultural product, such as the dramatic literature of a certain place, visibilizes the complexities of the psychological processes of a society, this research explores the ways in which subjectivities and associations between maternity and power are displayed in a group of texts of contemporary playwrights in Lima. The concept of the fertilizing man is suggested and some topics found throughout this literary corpus are discussed, such as women´s nutritious power, couple dynamics related to the abuse of power, the envy between the genders and the displacements of this battle for power, onto the descendence.